Expectations about alcohol effects and drinking pattern among high-school students - Martins, Raul Aragão; Parreira, Graziela Vanessa; Cruz, Luciana Aparecida Nogueira da; Silva, Izabella Alvarenga (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2010)
Studies have shown that adolescents begin to make use of alcoholic beverages earlier and excessively, a behavior which has several negative consequences. Thus, the present study aims at investigating whether the expectations they have for the effects of alcohol consumption are high or low and if there is a relationship between expectation and consumption pattern. AUDIT and IECPA were applied as data collection instruments. The first indentifies the pattern of alcohol use and the second investigates the expectations the subjects have in relation to the use of alcohol. The results of this study, differently than others, do not evidence the positive relationship between binge-drinking and high expectations about the use of alcohol.